2016
DOI: 10.17533/udea.rfo.v28n1a9
|View full text |Cite
|
Sign up to set email alerts
|

El profesionalismo en la formación odontológica

Abstract: ABSTRACT. Several authors as well as professional and educational institutions have advanced the issue of professionalism in the field of dentistry, agreeing that, even though professionalism plays a central role in the training of dentists, its incorporation in the curriculums INTRODUCCIÓNEntre las instituciones de educación superior, especialmente en aquellas dedicadas a la formación de profesionales de la salud, existe el consenso de que las competencias transversales y el profesionalismo son temas que debe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
6

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 48 publications
0
13
0
6
Order By: Relevance
“…clinical skills, competency-based education, dental competencies, dental curriculum, dental students, university students' professional attitudes determine how such students develop their professional practice in the future. 12 The early acquisition of these attitudes during dental school is essential so that graduates can practice professionally and ethically, delivering the best dental care to patients.…”
Section: Dental Professional Competenciesmentioning
confidence: 99%
“…clinical skills, competency-based education, dental competencies, dental curriculum, dental students, university students' professional attitudes determine how such students develop their professional practice in the future. 12 The early acquisition of these attitudes during dental school is essential so that graduates can practice professionally and ethically, delivering the best dental care to patients.…”
Section: Dental Professional Competenciesmentioning
confidence: 99%
“…Indeed, a large number of published studies across the health professions, demonstrated the positive effects of mentoring with regard to students' satisfaction, academic support, communication, professionalism and career advising 17–20 . Therefore, mentoring programme which was earlier a part of the hidden curriculum has now become a basic requirement for medical accreditation in national and international standards 2,17 …”
Section: Discussionmentioning
confidence: 99%
“…Professionalism is an essential attribute of contemporary healthcare education and a key element of clinical competency to provide high‐quality patient care 1 . In general, professionalism is defined as the ‘high standard that you expect from a person who is well trained in a particular job’ 2 . With regard to the healthcare profession, professionalism is considered to be a multidimensional concept with a commitment to one's work and an orientation towards service rather than personal profit 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para poder formar profesionales éticos en el campo de la salud, los temas deben ser enseñados en un ámbito educativo (Alcota et al, 2016). El curso en el que se adscriba debe contener objetivos definidos para el desarrollo de habilidades (Rossel et al, 2013) y, además, al ser una asignatura debe regirse según las características del currículo de la carrera, siendo una planificación que mejora la vivencia educativa del universitario (Wong & Nguyen, 2019).…”
Section: Introductionunclassified